Is institutional review board (IRB) doing its job right? How to assess this - Asif, Farah; Baig, Shahtaj (Journal of the Pakistan Medical Association, 2023)
Objectives: To audit the performance of the institutional review board at a cancer hospital. Method: The retrospective study was conducted at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, in 2021, and comprised all records of the institutional review board from 2005 to 2021. The audit was based on a tool created by the Association for the Accreditation of Human Research Protection Programmes, and elements evaluated included terms of reference, membership lists, review records, meeting minutes, institutional research guidelines as well as other relevant policies. Result: The institutional review board was found to be in 100% compliance with all the elements set forth in the Association for the Accreditation of Human Research Protection Programmes. The institutional review board was found to be an independent body with a diverse membership and the chairman was always an unaffiliated member. It had defined processes in line with relevant laws and guidelines. Review of research studies was devised to promote the ethical conduct of research. Conclusion: Though a self-assessment, the audit objectively showed that the institutional review board was in cent per cent compliance with the evaluation instrument developed and used by the Association for the Accreditation of Human Research Protection Programmes. Nevertheless, it still needs further discussion as to how high levels of efficiency and performance of institutional review boards ultimately provide a higher degree of protection to human research participants. Key Words: Ethics, Research, Ethics committees.